A companion to sport - Andrews, David L.; Carrington, Ben, 1972- (Chichester, West Sussex : Wiley Blackwell, 2013)
A Companion to Sport brings together writing by leading sports theorists and social and cultural thinkers, to explore sport as a central element of contemporary culture. Positions sport as a crucial subject for critical analysis, as one of the most significant forms of popular cultureIncludes both well-known social and cultural theorists whose work lends itself to an interrogation of sport, and leading theorists of sport itselfOffers a comprehensive examination of sport as a social and cultural practice and institution.
Further Reading6: Sports Medicine, Health, and the Politics of Risk; Introduction; Locating Sport in the Risk Society; Expect the Unexpected: Selling Safety; Anxiety, Assurance, and the Risk-Caution Citizenship Project; High Performance Sport and Health within the Risk Society; Conclusion; References; Further Reading; 7: Sport, Ecological Modernization, and the Environment; Environmental Issues and the Sociology of Sport: The "Early" Years; Sport, Sociology and the Environment: Contemporary Themes; Sport, the Environment, and Neoliberalism; Ecological Modernization and Environmental Sociology.
Edition statement from running title area.
Environmental Discourses and Promotional Culture: Examples from the Global Forum for Sports and the Environment.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed October 8, 2013).
Keywords: Sports -- Anthropological aspects; Sports -- Sociological aspects; Sports and society; Sports -- Anthropological aspects; Sports -- Sociological aspects; Electronic books